1982
DOI: 10.1037/0003-066x.37.5.504
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapy outcome: Smith and Glass' conclusions stand up under scrutiny.

Abstract: A sample of the original set of psychotherapy outcome studies analyzed by Smith and Glass was randomly selected for reanalysis to address criticisms of the methodological quality of the studies in the original sample. Each study was evaluated to see whether it had a no-treatment or placebo control group formed through random assignment. The subsample of studies judged to be appropriately controlled was then reanalyzed using Smith and Glass' meta-analytic procedures. The potential influence of statistical nonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0
2

Year Published

1985
1985
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(80 citation statements)
references
References 22 publications
(37 reference statements)
5
73
0
2
Order By: Relevance
“…It was then when discussions about common factors began to appear in psychology textbooks and manuscripts. Soon thereafter, several meta-analyses have illustrated the absolute efficacy of psychotherapy [50,[52][53][54]. Two important findings have been noted from those analyses, 1) that improved research methods did not increase the effects found and 2) that effect sizes were comparable across all treatments.…”
Section: Common Factors Modelmentioning
confidence: 91%
“…It was then when discussions about common factors began to appear in psychology textbooks and manuscripts. Soon thereafter, several meta-analyses have illustrated the absolute efficacy of psychotherapy [50,[52][53][54]. Two important findings have been noted from those analyses, 1) that improved research methods did not increase the effects found and 2) that effect sizes were comparable across all treatments.…”
Section: Common Factors Modelmentioning
confidence: 91%
“…At the same time, however, there is substantial evidence that supports the efficacy of the talking cure (Smith et al 1980;Landman and Dawes 1982;Mojtabai and Olfson 2008). Indeed, despite the decline of the talking cure in psychiatric practice, many psychiatric offices either have a resident psychotherapist to whom clients can be referred or have a list of recommended psychotherapists who can back up the physician's plan of treatment.…”
Section: How Does the Talking Cure Work?mentioning
confidence: 95%
“…In the broad sense of this word, traditional psychoanalysis and various forms of depth and humanistic psychologies count as psychotherapy, as do group therapy, role-playing therapies, journaling and other forms of treatment that emphasize the client's self-expression as having a curative effect. To say that psychotherapy is in decline, then, is to say that although a number of studies have demonstrated that talking to a patient is an effective form of treating mental problems (e.g., Smith and Glass 1977;Smith et al 1980;Landman and Dawes 1982;Mojtabai and Olfson 2008), traditional talking cures no longer are seen as offering the primary or best path to treating these problems. What takes center-stage today is a form of treatment, handled primarily by physicians, that uses pharmaceuticals to affect changes in brain chemistry.…”
Section: Introductionmentioning
confidence: 98%
“…Selon l'Organisation Mondiale de la Santé, cinq des dix principales causes d'incapacité dans le monde sont liées à des troubles mentaux. La recherche établit clairement que la psychothérapie est efficace pour résoudre de nombreux problèmes psychologiques ou d'adaptation (Smith, Glass, & Miller, 1980;Andrews & Harvey, 1981;Landman & Dawes, 1982;Shapiro & Shapiro, 1982;Lambert, Shapiro, & Bergin, 1994;Miller, Duncan, & Hubble, 1997;Wampold, 2001). Cette conclusion s'appuie sur de multiples recensions des écrits et de nombreuses méta-analyses couvrant 60 ans de travaux sur des milliers de personnes présentant un vaste éventail de problèmes traités par une variété d'approches.…”
Section: Continuum D'autodétermination 21unclassified